حماية الزوجة من جميع أشكال العنف -على ضوء التعديل الجديد لقانون العقوبات - تازير, آمنة (جامعة الوادي University of Eloued, 2019)
نهدف من خلال هذا المقال إلى تسليط الضوء على ظاهرة العنف ضد الزوجة، باعتبارها من أكثر الفئات عرضة للعنف داخل الأسرة، نتيجة لذلك تدخل المشرع الجزائري بصرامة تشريعية تجلت في ترسانة من النصوص القانونية، خصوصا تلك الواردة ضمن تعديل قانون العقوبات بالقانون 15/19 المؤرخ في 30 ديسمبر2015، الذي شدّد العقوبات إلى أقصاها على الزوج الممارس للعنف ضد زوجته بأي شكل (جسديا-نفسيا-اقتصاديا)، هذا القانون هدف المشرع من خلاله إلى ردع ظاهرة العنف الزوجي في الجزائر محاولا في ذلك التوفيق بين واجبه في حماية الزوجة من كل أشكال العنف من جهة، ورغبته في الحفاظ على كيان الأسرة من جهة ثانية، وعلى ما يبدوا أنه كان السبيل الأنجع لتحقيق ذلك رغم النقائص والانتقادات التي طالته. The aim of this research work is to highlight the issue of violence; Since the wife has become serenely harmed at home the Algerian legislator reacted with strict legislative measures; This is reflected in an arsenal of legal texts, especially those contained in the amendment to the Penal Code, Law 15/19 of 30 December 2015, which imposed maximum penalties on the husband who practices violence against his wife in any form (physically, psychologically and economically; the aim of the legislator is to deter the violent behavior of the husband and to try to put an end to this practice in Algeria by establishes a Reconciliation between the husband duties in protects the wife on the one hand; and to preserve the entity of the family on the other hand; this seems to be the mosh effectual way to achieve that despite criticisms and Deficiencies
protecting The Wife From All Forms Of Violence - In Light Of The New Amendment To The Penal Code
Keywords: العنف –الزوجة – العلاقة الزوجية – الأسرة- القانون.; violence- viscosity- marital relationship- family- law